Maslahah Mursalah in Ultra Petita Decision of The Constitutional Court - Endrik Safudin; Sesario Aulia (MUSLIM HERITAGE, 2025)
Ultra Petita refers to a court decision that goes beyond what was requested. Judges handling certain cases are limited to the issues raised by the parties involved. If the judge grants more than what was requested, the decision falls under Ultra Petita. In this context, the judge is only authorized to consider the claims and lawsuits based on those claims (iudex non ultra petita or ultra petita non cognoscitur). The judge only determines whether the issues at issue are true or false. Judges are prohibited from increasing or decreasing the demands and may not grant more than what is requested. This research aims to analyze two things. First, it discusses how the Constitutional Court's ultra petita decision is constructed. Second, it discusses how the principle of maslahah-mursalah is applied in the ultra petita decision of the Constitutional Court. By using descriptive analysis, the results show that the decisions of the Constitutional Court are an effort to protect the constitutional rights of citizens. Second, the ultra petita decision is in line with the principles of maslahah-mursalah. Ultra petita decisions allow constitutional judges to provide fair and valuable decisions and provide legal certainty.   Abstrak Ultra Petita mengacu pada keputusan pengadilan yang melebihi apa yang diminta. Hakim yang menangani kasus-kasus tertentu terbatas pada masalah yang diajukan oleh pihak-pihak yang terlibat. Jika hakim mengabulkan lebih dari yang diminta, keputusan tersebut termasuk dalam Ultra Petita. Dalam konteks ini, hakim hanya berwenang untuk mempertimbangkan tuntutan dan tuntutan hukum yang didasarkan pada tuntutan tersebut (iudex non ultra petita atau ultra petita non cognoscitur). Hakim hanya menentukan apakah isu yang dipermasalahkan benar atau salah. Hakim dilarang menambah atau mengurangi tuntutan dan tidak boleh mengabulkan lebih dari yang diminta. Penelitian ini Bertujuan menganalisis dua hal. Pertama, membahas bagaimana putusan ultra petita Mahkamah Konstitusi dikonstruksikan. Kedua, membahas bagaimana prinsip maslahah-mursalah diterapkan dalam putusan ultra petita Mahkamah Konstitusi. Dengan menggunakan analisis deskriptif, Hasil penelitian menunjukkan bahwa putusan-putusan Mahkamah Konstitusi merupakan upaya untuk melindungi hak-hak konstitusional warga negara. Kedua, putusan ultra petita sejalan dengan prinsip-prinsip maslahah-mursalah. Putusan ultra petita memungkinkan hakim konstitusi untuk memberikan putusan yang adil dan bernilai serta memberikan kepastian hukum.